The accidental mind - Linden, David J. 1961- (Belknap Press of Harvard University Press, 2007)
"A guide to the strange and often illogal world of neural function, 'The accidendal mind' shows how the brain is not an optimized, general-purpose problem-solving machine, but rather a weird agglomeration of ad-hoc solutions that have been piled on through millions of years of evolutionary history. Moreover Linden tells us how the constraints of evolved brain design have ultimately led to almost every transcendent human foible : our long childhoods, our extensnsive memory capacity, our search for love and long-term relationships, our need to create compelling narrative, and ultimately, the universal cultural impulse to create both religious and scientific explanations. With forays into evolutionary biology, this analysis of mental function answers some of our most common questions about how we've come to be who we are." - book jacket.